REKONSTRUKSI KONSEP ILMU DALAM AL-QUR’AN: ANALISIS TAFSIR TEMATIK DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM KONTEMPORER - Fanni Febria; Rahayu Yarlis Pratiwi; Agustiar (STKIP Subang, 2026)
The concept of knowledge in the Qur’an constitutes a fundamental foundation in building an Islamic civilization that integrates intellectual, spiritual, and moral dimensions. This study aims to analyze the concept of knowledge in the Qur’an through a thematic interpretation (tafsir maudhu’i) approach, covering its definition, position, sources, characteristics, and implementation in life. The method employed is a library research approach using descriptive-qualitative analysis of Qur’anic verses and recent scientific literature. The findings reveal that knowledge in the Qur’an is holistic in nature, deriving from revelation, reason, empirical experience, and reflection upon nature and history. Knowledge functions not only as a cognitive instrument but also as a pathway toward faith, moral development, and the advancement of civilization. Therefore, the integration of knowledge and divine values has become an urgent necessity within the context of contemporary Islamic education.